State of Hypophysis of Castrated Rats After Cryopreserved Ovarian Tissue Autotransplantation - Grischenko, V. I.; Saltovsky, D. V.; Lazurenko, V. V.; Gubina-Vakulik, G. I. (Problems of Cryobiology and Cryomedicine, 2002)
The results of an experimental investigation of hypophysis of castrated rats are presented. The application efficiency of autotransplantation of cryopreserved ovarian tissue (ACOT) when treating a post-castration syndrome (PCS) has been proved in animals.